Ship Maintenance Techniques for Removing Sea Barnacles That Stick to the Ship's Hull - Wijaya, Haryadi; Lefrandt , Lucia Ingrid Regina; Punuhsingon, Charles Stanley C. (Jurnal Ilmiah Platax, 2025)
The growth of marine biota such as barnacles attached to ship hulls is one of the main challenges in the shipping industry because it can increase hydrodynamic resistance, fuel consumption and accelerate corrosion of ship structures. This research aims to analyze the effectiveness of various ship maintenance techniques in removing sea barnacles and evaluate the advantages and challenges of each method used. The research method applied is a Systematic Literature Review (SLR) by analyzing previous studies discussing ship maintenance techniques in preventing and eliminating fouling. Data analysis was carried out using NVivo to identify research trends and VOSviewer to map relationships between methods used in previous studies. The research results show that the most effective approach in preventing the growth of barnacles is a combination of several methods, such as the use of silicone or fluorine-based paint which has low adhesion, ultrasonic technology which inhibits the colonization of marine biota, and a robot-based automatic cleaning system which can remove fouling without damaging the structure of the ship. This hybrid approach not only increases the fuel efficiency of ships but also helps reduce the impact of marine pollution due to the use of toxic chemicals. With the development of antifouling technology and the implementation of more innovative maintenance strategies, the shipping industry is expected to increase operational efficiency while supporting the long-term sustainability of the marine environment. Keywords: Ship Treatment, Antifouling, Ultrasonic Technology, Fouling, Hybrid Approach.